2000
DOI: 10.1111/1467-9582.00060
|View full text |Cite
|
Sign up to set email alerts
|

Triggers in L2 acquisition: The case of Spanish N‐N compounds

Abstract: Spanish has left-headed compounds which are not as productive as their left-headed counterparts in other languages. This presence or absence of productivity has been attributed to a binary parameter according to which N-N compounding, as opposed to nominal constructions in which the head noun takes a complement as in`the destruction of the city', would be the superset or marked option. Furthermore, the idiosyncratic nature of Spanish N-N compounding has been attributed to the make-up of Spanish Nouns. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
1
11
0
10
Order By: Relevance
“…At a later stage, they acquire the preposition de in the phrasal structure. The same result was also found in Liceras and Díaz (). Results of this current investigation outlined similar stages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At a later stage, they acquire the preposition de in the phrasal structure. The same result was also found in Liceras and Díaz (). Results of this current investigation outlined similar stages.…”
Section: Discussionsupporting
confidence: 89%
“…Liceras and colleagues examined the L2 acquisition of Spanish compounds by speakers of several L1s. For example, Liceras and Díaz () studied how native speakers of languages from both Indo‐European and non‐Indo‐European families acquire rare Spanish NN compounds. Using a picture naming task, they found that the L1 English group produced non‐Spanish compounds 46% of the time, and the non‐target performance was negatively correlated with proficiency, where intermediate and advanced learners' non‐target production was reduced to 25% and 9%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, these structures have to be head initial (N + PP)— zapatos de tango [shoes of tango] and fabricante de muñecas [maker of dolls]. Liceras and Díaz (), who studied these compounds, concluded that “their acquisition by English native speakers must be based on extremely limited positive evidence. Thus, it is not very surprising that even the advanced learners produced them only in about 60% of obligatory contexts” (as cited in Slabakova, , p. 516).…”
Section: Methodsmentioning
confidence: 99%
“…There is also experimental work on that relationship (Liceras and Díaz 2000;Liceras, Díaz, and Salomaa-Robertson 2002). However, to the best of our knowledge, there are no specific descriptions or analysis of the relationship between compounding and derivation in Spanish N-N compounds and this is so in spite of the fact that they offer an interesting ground for testing speakers' intuitions with respect to headness.…”
Section: Derivation and The Issue Of Headness In Spanish N-n Compoundsmentioning
confidence: 99%